Autoantibody profile in a cohort of South Indian children with Kawasaki disease - Suchetha Rao; Chaitanya Verma; Rathika Shenoy; Nutan Kamath (Wolters Kluwer Medknow Publications, 2014)
Objective: There is no clear data on autoantibody levels in Kawasaki Disease (KD) especially from the Indian Subcontinent. Aim: To look for the presence of organ nonspecific and organ specific antibodies to strengthen the search for an autoimmune cause of KD. We tested the presence of antinuclear antibody (ANA) and antithyroid microsomal antibody (TMA) in children with KD, 6 months after the acute phase. Anti Neutrophil Cytoplasmic Antibody (pANCA, cANCA), Anti Endothelial Cytoplasm Antibody (AECA) and Anti Smooth Muscle Antibody (SMA) was additionally tested in those with elevated titers of ANA and/or TMA. Materials and Methods: Prospective case-control study of 24 children with KD on follow up and an equal number of age and sex matched controls. Historical data about acute phase of illness was obtained from the medical records. After obtaining institutional ethics committee clearance and informed consent from the parents, blood was tested for ANA and TMA by the indirect immunofluorescence method (IIF), using a kit developed by Euroimmun. Positive samples were additionally tested for pANCA, cANCA, AECA and SMA. Relationship of autoantibody elevation and clinical course in the cases was determined. Results: The age of the study group was 4 ΁ 3.2 years. Incomplete KD was seen in 12.5% of the cases. Five cases (21%) had cardiac involvement. All but one with mitral and tricuspid regurgitation resolved after the acute phase of the disease. Only her ANA was elevated. Two children (8%) positive for TMA did not show any cardiac abnormalities. Further antibody testing was negative. All three children with elevated autoantibodies were females. (P value = 0.02: statistically significant). Conclusion: Elevated autoantibodies in three (12.5%) children after the acute phase may suggest the role of autoimmunity in the etiopathogenesis of KD, even though our observations were not statistically significant.